A global survey on the use of the international classification of diseases codes for metabolic dysfunction-associated fatty liver disease - DEMİRCİOĞLU, SERAP (My University, 2024)
Background: With the implementation of the 11th edition of the International Classification of Diseases (ICD-11) and the publication of the metabolic dysfunction-associated fatty liver disease (MAFLD) nomenclature in 2020, it is important to establish consensus for the coding of MAFLD in ICD-11. This will inform subsequent revisions of ICD-11. Methods: Using the Qualtrics XM and WJX platforms, questionnaires were sent online to MAFLD-ICD-11 coding collaborators, authors of papers, and relevant association members. Results: A total of 890 international experts in various fields from 61 countries responded to the survey. We also achieved full coverage of provincial-level administrative regions in China. 77.1% of respondents agreed that MAFLD should be represented in ICD-11 by updating NAFLD, with no significant regional differences (77.3% in Asia and 76.6% in non-Asia, p = 0.819). Over 80% of respondents agreed or somewhat agreed with the need to assign specific codes for progressive stages of MAFLD (i.e. steatohepatitis) (92.2%), MAFLD combined with comorbidities (84.1%), or MAFLD subtypes (i.e., lean, overweight/obese, and diabetic) (86.1%). Conclusions: This global survey by a collaborative panel of clinical, coding, health management and policy experts, indicates agreement that MAFLD should be coded in ICD-11. The data serves as a foundation for corresponding adjustments in the ICD-11 revision. Keywords Global survey · MAFLD · ICD-11
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Gastroenteroloji-(Hepatoloji); Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Gastroenterology and Hepatology; Health Sciences; Klinik Tıp (Med); Klinik Tıp; Gastroenteroloji Ve Hepatoloji; Clinical Medicine (Med); Clinical Medicine; Gastroenterology & Hepatology; Hepatoloji; Hepatology; Global survey; ICD-11; MAFLD